2022
DOI: 10.3390/agronomy12051163
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Analysis of Two Contrasting Rice Genotypes in Response to Salt Stress

Abstract: Improving rice salt-tolerance is an effective way to deal with the increasing food demand caused by soil salinization and population growth. Nevertheless, the molecular mechanisms of rice salt-tolerance remain elusive. In this study, comparative transcriptomic analyses were performed to identify salt-tolerance genes that were either specifically regulated or more changed in salt-tolerant cultivar FL478 relative to salt-sensitive cultivar 93-11. In total, 1423, 175, and 224 salt-tolerance genes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Globally, our analysis of the RNA‐seq data revealed a reduction of approximately 21% and 32% in the number of differentially expressed and differentially spliced genes, respectively, clearly showing that ABA induced fewer changes not only in gene expression but also in alternative splicing in the least ABA‐sensitive accession, Kn‐0. Transcriptomic studies comparing natural variants with opposite stress sensitivities have been essentially conducted in other plant species and with inconsistent results—genotypes more sensitive to an osmotic stressor, such as salt, do not always change their expression and splicing patterns in response to stress than tolerant cultivars (Kaundal et al., 2021; Kong et al., 2021; Li et al., 2018; Mirdar Mansuri et al., 2019; Shankar et al., 2016; Ye et al., 2022; Zhang et al., 2021). Nonetheless, these studies largely agree on the importance of the stress‐tolerant variant activating genes with relevant stress functions.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, our analysis of the RNA‐seq data revealed a reduction of approximately 21% and 32% in the number of differentially expressed and differentially spliced genes, respectively, clearly showing that ABA induced fewer changes not only in gene expression but also in alternative splicing in the least ABA‐sensitive accession, Kn‐0. Transcriptomic studies comparing natural variants with opposite stress sensitivities have been essentially conducted in other plant species and with inconsistent results—genotypes more sensitive to an osmotic stressor, such as salt, do not always change their expression and splicing patterns in response to stress than tolerant cultivars (Kaundal et al., 2021; Kong et al., 2021; Li et al., 2018; Mirdar Mansuri et al., 2019; Shankar et al., 2016; Ye et al., 2022; Zhang et al., 2021). Nonetheless, these studies largely agree on the importance of the stress‐tolerant variant activating genes with relevant stress functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al reported 17 TFs as hub genes of maize drought stress adaptation with WGCNA [28]. Moreover, one and nine candidates hub TFs related to salt response in rice have been detected using WGCNA [29,30]. Likewise, the use of WGCNA focused on the study of hub TFs has helped to improve the response of plants to abiotic stress.…”
Section: Introductionmentioning
confidence: 99%